Pain severity, demographic factors, expectation and patients' satisfaction toward postoperative abdominal pain management by health team - O Chaichart (Journal of Health Science and Medical Research (JHSMR), 2006)
This descriptive research aimed to describe pain intensity, demographic factors, and patients' satisfaction with and expectation about postoperative abdominal pain management by the health team. The sample consisted of 165 abdominal postoperative patients from two regional hospitals in southern Thailand. The results of the research revealed that overall patients' expectation about postoperative abdominal pain management by the health team was reached. Overall mean score of what was expected or desired was at a low level and what was actually received was at a moderate level. Overall mean scores of patients' satisfaction with postoperative abdominal pain management by the health team, by physicians and by nurses were at a high level. Demographic variables, pain intensity, and patients' expectation about postoperative abdominal pain management by physicians and by nurses together accounted for 20% of the variance in the patients' satisfaction with postoperative abdominal pain management by the health team (adjusted R2 = .20, p < .01). Demographic variables, pain intensity, and patients' expectation about postoperative abdominal pain management by physicians and by nurses accounted for 21% and 14% of the variance in the patients' satisfaction with postoperative abdominal pain management by physicians and by nurses respectively (adjusted R2 = .21, p < .01, adjusted R2 = .14, p < .01 respectively). The result suggested that health team including physicians and nurses should assess patients' expectation about postoperative abdominal pain management. In addition, preoperative and postoperative patient education should be given together with information regarding pain management and an appropriate manual.